2014
DOI: 10.1016/j.ajog.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Uterine cellular leiomyomata with chromosome 1p deletions represent a distinct entity

Abstract: OBJECTIVE This study aims to determine whether 1p deletion defines a subset of cellular leiomyomata (CL), a hypercellular variant of uterine leiomyomata (UL) that may have delayed malignant potential, and correlate this genetic change with clinical and pathologic characteristics including those present in uterine sarcomas. STUDY DESIGN Available CL cases at Mayo Clinic (n=101) and variant cases reported by Giuntoli et al. (n=16) were identified. Each case with sufficient tissue that met histologic criteria f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Deletions of 1p have been associated with distinct histopathological features and possible malignant progression of leiomyomas (11,16). Interestingly, we identified NPHP4 as the most commonly deleted gene on chromosome 1p.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Deletions of 1p have been associated with distinct histopathological features and possible malignant progression of leiomyomas (11,16). Interestingly, we identified NPHP4 as the most commonly deleted gene on chromosome 1p.…”
Section: Discussionmentioning
confidence: 78%
“…Leiomyomas frequently harbor recurrent deletions affecting 7q22, 22q, and 1p, suggesting that these regions contain tumor suppressor genes (8)(9)(10)(11). High-throughput sequencing studies have rarely detected second hit mutations within these regions, however (3,4,13), suggesting that the target genes may act in a haploinsufficient manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New evidence of increased mitotic index and chromosome 1p deletions may lead treating physicians to a more aggressive and more intense follow up as these have been shown to have more malignant potential and likely increased recurrence rate [16,42]. Recommendations include the following: if a patient has been diagnosed with STUMP after tissue sample from biopsy or hysteroscopy, the surgeon should perform a hysterectomy on the patient (regardless of vaginal, abdominal, or laparoscopic).…”
Section: Treatment and Post-treatment Follow Upmentioning
confidence: 99%
“…Mehine et al and Hodge et al confirmed a malignant behavior in myometrial cells containing the chromosome 1p deletion. Further identification and classification of chromosomal mutations and signaling pathways will aide in correct diagnosis and management [11,16,17].…”
Section: Pathophysiologymentioning
confidence: 99%